Peningkatkan Kemampuan Membaca Permulaan dengan Mengggunakan Media Flashcard untuk Anak Autis Kelas III - Widiyantari, Widiyantari; Z, Martias (Jurnal Penelitian Pendidikan Khusus, 2022)
This study discusses how to improve early reading skills by usingflashcard media for third grade autistic children at SLBN TanjungJabung Timur. This type of research uses classroom action research.The problem behind this research is the class III SLBN TanjungJabung Timur the inability of children to learn to read early and thelevel of concentration and sitting endurance of autistic children is lowand lacks interest in learning to read. This research will be carried out in two cycles, in each cycle consisting of planning, action, observation and reflection. The data collection technique used is in the form of observation, documentation, and action. The results obtained by students in two cycles are 83.3%, in the first cycle the action gets 62.5% and in the second cycle the score is 83.3%. Based on these data, the conclusion obtained is that children experience an increase in initial reading through flashcard media